2021
DOI: 10.20944/preprints202103.0010.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emotional Performance of a Low-Cost Eco-Friendly PBL Methodology for Science Education. Approach in Prospective Teachers

Abstract: The emotional dimension in education has become increasingly important in recent decades. Enhancing the emotional dimension of prospective teachers in science subjects is higher education stuff responsibility. The implementation of active methodologies could modify the traditional student-teacher roles that are encouraged by the educational policies implemented in the Bologna Process. The principal aim of this work is to describe a Project Based Learning methodology and to introduce it as potential resource fo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Their limitations in understanding physics material affect their confidence in correctly conveying it to students. Emotions toward Physics, such as fear or rejection of specific science topics, can also reduce self-efficacy in teaching (Hernández-Barco et al, 2021).…”
Section: Prospective Physics Teachers' Self-efficacy In Each Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…Their limitations in understanding physics material affect their confidence in correctly conveying it to students. Emotions toward Physics, such as fear or rejection of specific science topics, can also reduce self-efficacy in teaching (Hernández-Barco et al, 2021).…”
Section: Prospective Physics Teachers' Self-efficacy In Each Domainmentioning
confidence: 99%
“…Several studies have shown that self-efficacy is not affected by gender differences (Hernández-Barco et al, 2021;Özdemir & Hastürk, 2021;Shahat et al, 2022). Self-efficacy increases with age and length of teaching experience (Kahveci et al, 2018), besides that it can also be improved through specific learning approaches (González-Gómez et al, 2022;Mukhtar et al, 2021).…”
Section: Introductionmentioning
confidence: 99%